1987
DOI: 10.1161/01.res.61.2.280
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of histamine actions in human coronary arteries.

Abstract: Helical strips of human coronary arteries contracted in response to histamine concentration dependently, they relaxed with low concentrations and contracted with high concentrations. Treatment with cimetidine potentiated contraction in the strips with intact and damaged endothelium to a similar extent and attenuated relaxation. Removal of endothelium abolished relaxation and potentiated contraction in the cimetidine-treated strips. Methylene blue increased the contractile response to histamine in the strips wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
50
0
6

Year Published

1988
1988
2003
2003

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(58 citation statements)
references
References 20 publications
2
50
0
6
Order By: Relevance
“…Under conditions of dysfunctional eNOS, the histamine-induced vasorelaxation is converted into a contraction, which is mediated via H 1 receptors on smooth muscle cells. 9,26 Histamine-induced vasoconstriction has also been observed in atherosclerotic coronary arteries 26 -28 and may contribute to the onset of an acute coronary syndrome. Interestingly, an increased histamine content has been found in atherosclerotic coronary segments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under conditions of dysfunctional eNOS, the histamine-induced vasorelaxation is converted into a contraction, which is mediated via H 1 receptors on smooth muscle cells. 9,26 Histamine-induced vasoconstriction has also been observed in atherosclerotic coronary arteries 26 -28 and may contribute to the onset of an acute coronary syndrome. Interestingly, an increased histamine content has been found in atherosclerotic coronary segments.…”
Section: Discussionmentioning
confidence: 99%
“…7 By occupying H 1 receptors on endothelial cells, histamine activates endothelial nitric oxide synthase (eNOS). 8 The nitric oxide (NO) produced by eNOS dilates all kinds of blood vessels, including human coronary arteries, 9 and has protective effects against platelet and leukocyte adhesion and smooth muscle proliferation and, thus, probably atherosclerosis. 10 However, the direct activation of eNOS by histamine represents a short-term and probably transient action of the amine.…”
mentioning
confidence: 99%
“…On the other hand, histamine induces a reduction of coronary vascular resistance (Vigorito et al 1986). Recently, three different histamine receptor mechanisms have been reported in the human coronary artery (Toda 1987). If these three components differ depending on the size of the coronary vessel, previously conflicting data are conceivable.…”
mentioning
confidence: 99%
“…Toda (1987) suggested that relaxation to histamine was mediated by both HI receptors on the endothelium and H2 receptors in the smooth muscle, but that the response was complicated by contraction via HI receptors on the muscle at high concentrations of histamine (0.1 4M and above). Consequently, biphasic curves have often been reported (Toda, 1987;Toda & Okamura, 1989). In this study, however, no contraction responses were observed, even at high concentrations of histamine (1-1OIM), except in the absence of endothelium, indicating that EDRF release (via endothelial HI receptors) and stimulation of the (relaxing) H2 receptors was overriding the direct constrictor effect on the smooth muscle.…”
Section: L-arginine Analoguesmentioning
confidence: 99%
“…Acetylcholine has been shown to be a sensitive marker of endothelial dysfunction with early atheroma (Vita et al, 1990;Zeiher et al, 1991), whilst substance P is a powerful vasodilator agent which can increase arterial diameter by up to 30% (Crossman et al, 1989). Toda (1987) demonstrated a relaxation response to substance P in human coronary artery helical strips in vitro, and release of EDRF by histamine in the same tissue. Bradykinin, the calcium ionophore A23 187 and, occasionally, acetylcholine, have also been shown to relax human coronary artery in vitro (F6rstermann et al, 1988).…”
Section: Introductionmentioning
confidence: 99%